Application of mathematical modeling in the construction of the ecological house and the teachers' perspectives in this teaching trend - Marques, Caio Vieira; Oliveira, Ana Maria Libório de; Santos, Crisonéia Nonata Gomes dos; Lima, Érika de Oliveira; Field´s , Karla Amâncio Pinto; Alves, Tiago Felipe de Oliveira (Seven Editora, 2023)
The investigation was carried out in a public school in the Federal District, located in the Structural Administrative Region, in the period of one year, to verify the perspectives of the teaching trend Modeling and a reflection of mathematics interacting with an environmental conscience. The article intends to disseminate the results of the research carried out on Mathematical Modeling and promoted with the incentive of the Scientific Initiation Program (PIBIC) of the Federal Institute of Education, Science and Technology of Brasília – structural campus. The investigation aimed to identify the methodology most used by mathematics teachers and how the discipline was approached, as well as to carry out the creation of an ecological model. The methodology was bibliographic reviews, questionnaires for teachers, intervention through the production of a model and reinforcement strategies for students in mathematics content, aiming to promote a different perspective on how to solve the proposed activities and introduce the basic concepts of geometry , with the vision of applying several objects with different geometric shapes for the construction of the model. Regarding the teaching trend of Mathematical Modeling, the teachers who answered the questionnaire stated that they did not know this methodology, at least with this name. Furthermore, it was identified that most of the classes were transmitted in the traditional way, that the teachers did not feel comfortable using new methodologies and/or methods, so that the meetings and the production of the model collaborated effectively for the student and teacher learning in the contents related to the recycling of sustainable materials,  in order to innovate activities proposed in the classroom. DOI:https://doi.org/10.56238/ptoketheeducati-010